CDK4/6 inhibition suppresses tumour growth and enhances the effect of temozolomide in glioma cells - Cao, Yingxiao (J Cell Mol Med, 2020)
In adults, glioma is the most commonly occurring and invasive brain tumour. For malignant gliomas, the current advanced chemotherapy includes TMZ (temozolomide). However, a sizeable number of gliomas are unyielding to TMZ, hence, giving rise to an urgent need for more efficient treatment choices. Here, we report that cyclin‐dependent kinases 4 (CDK4) is expressed at significantly high levels in glioma cell lines and tissues. CDK4 overexpression enhances colony formation and proliferation of glioma cells and extends resistance to inhibition of TMZ‐mediated cell proliferation and induction of apoptosis. However, CDK4 knockdown impedes colony formation and cell proliferation, and enhances sensitivity of glioma cells to TMZ. The selective inhibition of CDK4/6 impedes glioma cell proliferation and induces apoptotic induction. The selective inhibitors of CDK4/6 may enhance glioma cell sensitivity to TMZ. We further showed the possible role of RB phosphorylation mediated by CDK4 for its oncogenic function in glioma. The growth of glioma xenografts was inhibited in vivo, through combination treatment, and corresponded to enhanced p‐RB levels, reduced staining of Ki‐67 and enhanced activation of caspase 3. Therefore, CDK4 inhibition may be a favourable strategy for glioma treatment and overcomes TMZ resistance.